Effect of Leachate Concentration on the Eichhornia Crassipes Plants - Irhamni Irhamni; Edison Purba; Wirsal Hasan (Fakultas Teknik, 2023)
Increase in science and technology development today has spurred environmental pollution in water, soil and air. Water pollution caused by the impact of industrial development must be controlled as quickly as possible. The study aimed to investigate the effect of Eichhornia crassipes plants at given metal concentrations. The Eichhornia crassipes plant was used as an observation material with varying concentrations of metal (Cr, Hg, and Pb). The method used in this study was Randomised Block Design (RBD) and continued with Duncan's Multiple Range Test analysis, or better known as the DMRT test. The study observations showed that the increase in Eichhornia crassipes seedlings was 3cm, 2cm and 2cm, respectively with the recorded concentrations of 20%, 40%, 60%, and 80%. Meanwhile, the leachate concentrations of 20%, 40%, 60%, and 80% could also increase the roots of Eichhornia crassipes plants by 3.5cm, 1.5cm and 1cm, respectively. However, the leaf growth of Eichhornia crassipes plants at concentrations of 20% and 40% recorded as much as three and two leaves only. Additionally, it can be noted that at leachate concentrations of 20% and 40%, there was an increase in the number of Eichhornia crassipes leaf petals during observation. Overall results showed that low concentrations could increase the Eichhornia crassipes plants. This was evident in the statistical test analysis, where the leachate concentration in the Eichhornia crassipes plant affected the overall test results.